An Ultrasonic System for Determining Mango Physiological Properties - Sallehuddin Ibrahim; Mohd Amri Md Yunus; Mohd Taufiq Md Khairi; Aini Hazwani Mohd Zelan (Proceeding of the Electrical Engineering Computer Science and Informatics, 2015)
There is an increasing requirement for high qualityfruits such as mango. Hence it is vital to have a fast, accurate andreliable method for measuring and monitoring the quality of fruitfrom the field to the consumer. This paper presents aninvestigation on the use of an ultrasonic measurement system fordetermining the quality of mango.